Antioxidant Activity of Different Phenolic-Rich Fractions Obtained From Peels of Turkish Dark Purple Eggplant - Djouadi, Assia; Yilmazer, Hakan; Djouadi, Anfal; Cakir, Bilal (WILEY, 2025)
This study investigated the extraction of phenolic compounds and the antioxidant potential of eggplant peel using various extraction methods and GRAS solvent systems. Ethanol absolute and (EtOH: water) (70:30) system solvents were used separately to extract phenolic compounds, while the (EtOH: water: citric acid) (70:30:0.5) system was utilized for anthocyanin extraction. Otherwise, to test the antioxidant activity of anthocyanin separately, an aqueous anthocyanin-rich fraction was recovered from eggplant peel crude extract using successive liquid/liquid extractions with solvents of different polarities. The presence of total phenolics, anthocyanins and proanthocyanidin were detected, and HPLC analysis was realized. The antioxidant activity was performed by the (DPPH) free radicals method. Soxhlet extraction using absolute ethanol provides a high yield of phenolic compounds. Otherwise, the anthocyanin extract showed a high level of anthocyanin contents. The liquid chromatographic analysis presented an important percentage of flavonoids. Soxhlet extract was the most effective in scavenging free radicals.
Keywords: DPPH antioxidant activity; eggplant skin; extraction; HPLC; polyphenols; spectrophotometry; SOLANUM-MELONGENA L.; ULTRASOUND-ASSISTED EXTRACTION; SOXHLET EXTRACTION; ANTHOCYANINS; FRUIT; OPTIMIZATION; RECOVERY; ACIDS; CAPACITIES; PRODUCTS; Food Science & Technology